ALPHA GENERATION'S LANGUAGE ATTITUDES IN INDONESIAN DIGITAL LITERACY PRACTICES - Goziyah; Hayatun Nufus (Akrab Juara : Jurnal Ilmu-ilmu Sosial, 2026)
The rapid development of digital technology has influenced literacy practices and language use among Generation Alpha. This phenomenon affects their language attitudes toward the Indonesian language in digital spaces. This study aims to describe the language attitudes of Generation Alpha in Indonesian digital literacy practices. The research employed a descriptive qualitative method. Data were collected through observation of digital literacy activities, questionnaires, and interviews with Generation Alpha students. Data analysis involved data reduction, data display, and conclusion drawing. The findings reveal that Generation Alpha demonstrates varied language attitudes, including positive, neutral, and negative attitudes. Positive attitudes are reflected in the functional and communicative use of Indonesian, while negative attitudes appear in the excessive use of foreign languages and code-mixing. This study concludes that digital literacy plays a significant role in shaping Generation Alpha’s language attitudes, highlighting the need to strengthen digital literacy education oriented toward the preservation of the Indonesian language